1998
DOI: 10.1046/j.1365-2133.1998.02115.x
|View full text |Cite
|
Sign up to set email alerts
|

Minoxidil upregulates the expression of vascular endothelial growth factor in human hair dermal papilla cells

Abstract: The hair follicle dermal papilla which controls hair growth, is characterized in the anagen phase by a highly developed vascular network. We have demonstrated in a previous study that the expression of an angiogenic growth factor called vascular endothelial growth factor (VEGF) mRNA varied during the hair cycle. VEGF mRNA is strongly expressed in dermal papilla cells (DPC) in the anagen phase, but during the catagen and telogen phases. VEGF mRNA is less strongly expressed. This involvement of VEGF during the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
4
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(158 citation statements)
references
References 20 publications
4
132
4
9
Order By: Relevance
“…Kwack et al 27 found that the phosphorylation of GSK3β, PKA, and PKB and expression of Axin2, Lef-1, and EP2 were accelerated by minoxidil in HFDPC. Lachgar et al 28 demonstrated that minoxidil in the range of 0.2 to 12 µM raised VEGF mRNA expression and protein in HFDPC. Previously, no concrete molecular evidence existed that minoxidil directly affects the upregulation/downregulation of DKK-1, IGF-1, TGF-β2, and Wnt5α.…”
Section: Discussionmentioning
confidence: 99%
“…Kwack et al 27 found that the phosphorylation of GSK3β, PKA, and PKB and expression of Axin2, Lef-1, and EP2 were accelerated by minoxidil in HFDPC. Lachgar et al 28 demonstrated that minoxidil in the range of 0.2 to 12 µM raised VEGF mRNA expression and protein in HFDPC. Previously, no concrete molecular evidence existed that minoxidil directly affects the upregulation/downregulation of DKK-1, IGF-1, TGF-β2, and Wnt5α.…”
Section: Discussionmentioning
confidence: 99%
“…An VEGF mRNA is strongly expressed in DP cells during anagen phase with a substantial decrease of expression during catagen and telogen phases Topical minoxidil on the hair follicle can increased the expression of VEGF mRNA, presented in the DP cells [49,73,74].…”
Section: Minoxidilmentioning
confidence: 99%
“…Lachgar, et al [73] performed a study to evaluate if minoxidil could affect the expression of VEGF. According to the authors, minoxidil caused an elevation of VEGF and should be consider an indirect inducer of angiogenesis through an up regulation of the expression of VEGF in DP cells, during the anagen phase.…”
Section: Minoxidilmentioning
confidence: 99%
“…17,20 Ketoconazole topical treatment was observed to promote hair growth by increasing density and size of anagen follicles when used over period of 21 weeks at a concentration of 2% in a shampoo formulation. Though anti-DHT activities of ketoconazole have been reported, the major beneficial effects were suggested to be arising from its inhibitory actions on inflammation and fungal infections in the scalp.…”
Section: Ant-inflammatory Antioxidant and Antimicrobial Agents Ketocmentioning
confidence: 99%
“…Minoxidil is also reported to promote angiogenesis by enhancing VEGF mRNA expression in dermal papilla. 20 In in vitro settings, minoxidil stimulates PGE2 and leukotriene B4 expression, and block prostacyclin production in by dermal papilla cells. Also the expression of EP2, one of the PGE2 receptors responsible for lengthening of anagen phase is amplified under the influence of minoxidil treatment.…”
Section: Minoxidilmentioning
confidence: 99%